2017
DOI: 10.4102/jomped.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary leaf epidermal and pollen morphology of some West African species of <i>Desplatsia</i> Bocq

Abstract: Desplatsia is a genus made up of about four to eight species which are mostly trees native to tropical Africa. The leaf and pollen characters of three West African species of Desplatsia were investigated using light microscopy. The study was aimed at investigating the leaf epidermis and pollen morphology of the species to further enhance the understanding of the taxonomic relationships in the genus. The epidermal cells were isodiametric, polygonal to irregular with straight, curved to wavy anticlinal cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There has been some documentation in which epidermal markers were used to discriminate plant taxa [14,[16][17][18][19]. Results obtained from this study clearly demonstrated that epidermal markers could provide a reasonable value for discriminating the selected medicinal tree species of apocynaceae.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…There has been some documentation in which epidermal markers were used to discriminate plant taxa [14,[16][17][18][19]. Results obtained from this study clearly demonstrated that epidermal markers could provide a reasonable value for discriminating the selected medicinal tree species of apocynaceae.…”
Section: Discussionmentioning
confidence: 57%
“…Other useful qualitative markers with taxonomic value based on the result include stomatal abundance, anticlinal wall and crystal types, which varied among the species. Such markers could be employed at both specific and generic level of the medicinal species as previously reported in some plant's families [13,17]. The overlap in the epidermal cell shape of these species makes it unsuitable as a marker for taxonomic purpose in the taxa.…”
Section: Discussionmentioning
confidence: 99%